Cloning and expression of a novel synthetic gene containing VP1 and 3A in Bacillus subtilis as a vaccine candidate against foot-and-mouth disease virus. (July 2019) - Aghaei, Afsaneh; Moghbeli, Majid; Kargar, Mohammad; Nazarian, Shahram; Kafilzadeh, Farshid
Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease of livestock animals and control of the disease based on vaccination against serotypes O, A and Asia 1 is important. VP1 (structural) protein and 3A (non-structural) protein is the important antigen in FMDV and they can be used to design recombinant vaccines. In this study the bioinformatics characteristics of VP1 [141–160 and 23–42] and 3A [21–35] of Iranian serotypes O, A and Asia 1 was obtained using on-line predicting software. Then the sequence VP1 [141–160]-GS-VP1 [23–42]-GS-3A [21–35]-GS were codon-optimized and cloned onpHT43shuttle vector and finally expressed in Bacillus subtilis WB600 strain. We could predict VP1 [141–160] as a B cell epitope, VP1 [23–42] as a CTL epitope and 3A [21–35] as a Th cell epitope. The 20KD recombinant protein expressed by Bacillus subtilis were detected by SDS-PAGE. The results showed that this recombinant protein had epitope characteristics and it could be useful as a vaccine candidate to control all serotypes of FMD in Iran.